2017
DOI: 10.3892/mmr.2017.8170
|View full text |Cite
|
Sign up to set email alerts
|

Oxysophoridine rescues spinal cord injury via anti‑inflammatory, anti‑oxidative stress and anti‑apoptosis effects

Abstract: Oxysophoridine (OSR) is an alkaloid extracted from Sophora alopecuroides L and has various pharmacological activities. The present study aimed to investigate the protective effects and underlying mechanisms of OSR on spinal cord injury (SCI), a clinically common serious trauma, in a rat model. The results of the present study demonstrated that the anti‑inflammatory effect of OSR improved Basso, Beatie and Bresnahan Locomotor Rating Scale scores and reduced spinal cord tissue water contents in an SCI rat model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
9
0
3
Order By: Relevance
“…Inflammation, apoptosis, and oxidative stress contribute to the secondary damage of SCI [180]. Pharmacological interventions that mitigate the secondary phase process may provide the therapeutic efficacy for SCI [181]. Shi et al indicated that the administration of naringenin ameliorated SCI by down-regulating mir-223, and decreasing tissue myeloperoxidase, as a marker of neutrophil infiltration, as well as abrogating inflammatory cytokines [182].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Inflammation, apoptosis, and oxidative stress contribute to the secondary damage of SCI [180]. Pharmacological interventions that mitigate the secondary phase process may provide the therapeutic efficacy for SCI [181]. Shi et al indicated that the administration of naringenin ameliorated SCI by down-regulating mir-223, and decreasing tissue myeloperoxidase, as a marker of neutrophil infiltration, as well as abrogating inflammatory cytokines [182].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Travma sonucu oluşan hücresel zedelenme, serbest radikallerin oluşumunu arttırır [8]. MDA düzeyi, oksidatif stresin bir göstergesi olarak bilinmektedir [4,5,9]. Gal ve arkadaşlarının çalışmasında postoperatif erken dönemde MDA değerleri laparoskopik grupta anlamlı olarak düşük bulunmuştur [4].…”
Section: Gereç Ve Yöntemunclassified
“…MDA düzeyi, oksidatif stresin bir göstergesi olarak bilinmektedir [4,5,9]. Gal ve arkadaşlarının çalışmasında postoperatif erken dönemde MDA değerleri laparoskopik grupta anlamlı olarak düşük bulunmuştur [4]. Çalışmamızda ise gruplar içinde MDA değerleri açısından anlamlı farklılık bulunmamakla birlikte postoperatif 24. saatteki değerler literatürle uyumlu olarak açık operasyonlarda anlamlı olarak daha yüksekti.…”
Section: Gereç Ve Yöntemunclassified
See 1 more Smart Citation
“…Oxysophoridine is an alkaloid extracted from Sophora alopecuroides Linn. Many studies based on in vitro cellular or in vivo animal assays have shown that oxysophoridine has various pharmacological activities, including suppression of the growth of hepatocellular carcinoma [ 10 ] and colorectal cancer cells [ 11 ] by regulating apoptosis associated with the Bcl-2/Bax/caspase-3 signalling pathway, and alleviation of spinal cord injury via anti-inflammatory, anti-oxidative stress and anti-apoptosis effects [ 12 ]. In the present study, we found a new indication for oxysophoridine as a compound inhibiting SARS-CoV-2 infection in cell culture.…”
mentioning
confidence: 99%